Corrosion failure analysis of the heat exchanger in a hot water heating boiler. (December 2022) - Liu, Shijie; Wu, Haomin; Zhao, Qinxin; Liang, Zhiyuan
Highlights: The main corrosion failure reasons of 20G tube are internal oxidation and under-deposit corrosion. High hardness water continuously deposits corrosion on the tube surface. Dissolved oxygen forms many local electrochemical battery on the tube surface, leading to the occurrence of perforation. Cl - penetrates into the interior of the tube, causing local acid corrosion and further deepening the damage to the matrix. Abstract: The corrosion failure of the heat-exchanger made of 20G steel in a hot water heating boiler was investigated. The morphology and phase compositions of the corrosion products were analyzed using X-ray diffraction (XRD), scanning electron microscope (SEM) with energy disperse spectroscopy (EDS). The results showed that the boiler feed water did not meet the water quality standard, which contained excessive ion concentrations of Ca and Mg and dissolved oxygen content. At the surface of failed tubes, loose corrosive products containing numerous cracks provided micro-channels for Cl - diffusion into the matrix of 20G steel, thus leading to the local electrochemical reaction. This continuous and Cl-induced electrochemical erosion at some positions led to a vicious cycle which caused more severe damage to the tube, finally resulting in a perforation failure of the tube. To avoid this kind of accident happening, some suggestions are given in this paper.